Influence of screw angle and position on the extraction dynamics of Cross-Laminated Timber: an empirical analysis and comparative modeling study - Jia Lei; Xinran Li; Xinmeng Wang; Feibin Wang; Shuo Wang; Xin An; Meng Gong; Zeli Que (Journal of Asian Architecture and Building Engineering)
The design of dowel-type fastener connections is crucial for the structural integrity of Cross-Laminated Timber (CLT) systems, with individual fastener anchorage capacity as a key factor. This study investigates the withdrawal performance of Self-Tapping Screws (STSs) in CLT systems using Canadian Douglas fir. Four driving angles—45°, 60°, 75°, and 90°—were tested, alongside screw placements within panel gaps. Optimal performance was observed at 75° and 90°, with 90° placement in gaps enhancing stiffness and ductility but reducing energy dissipation. The ratios of experimental capacities to model predictions were 1.26–1.49 for the Blaß and Uibel (B&U) model and 1.36–1.56 for Eurocode 5 (EC5). The new EC5 code, compared to the previous version, includes several advancements such as more accurate material properties and improved calculation methods for fastener withdrawal capacity, offering enhanced prediction accuracy for STS performance in CLT. The discrepancies in the over-strength factors predicted by the new EC5 version ranged from 1.07 to 1.37. These findings suggest the need to consider the incorporation of a specific calculation model for STS withdrawal capacity in CLT, such as the Ringhofer et al. model, in the next revision of EC5.